Correlation dependences between short-term/long-term static strength characteristics and creep resistance of tungsten at high temperatures - Borisenko, V.A.; Bukhanovskii, V.V.; Mamuzic, I. (Проблемы прочности, 2005)
Experimental data on high-temperature mechanical properties under uniaxial tension of commercially pure tungsten obtained by powder metallurgy have been analyzed. It has been found that for powder metallurgy tungsten in the high-temperature region ~ (0.5 — 08)Tmelt, there is a close correlation among the characteristics of short- and long-term static strengths and creep resistance, which are described by a single functional relation.